2018
DOI: 10.1016/j.molimm.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Caspases are key regulators of inflammatory and innate immune responses mediated by TLR3 in vivo

Abstract: Understanding the key regulators which impact the innate immune response during initial phases of tissue injury, can advance the use of therapeutic approaches which aim at attenuating inflammation and organ damage. Recognition of microbial components by TLRs, initiates the transcription of innate immune signal pathways, that induce the expression of key inflammatory mediators: cytokines, chemokines and adhesion molecules. Beside regulating apoptotic cell death, recent studies have revealed distinct roles for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Recent studies propose a close association of inflammation and cell death [21, 22]. Induction of cell death in HBMEC is a mechanism some pathogens employ, presumably to gain entrance into the CNS by an impairment of BBB integrity [2327].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies propose a close association of inflammation and cell death [21, 22]. Induction of cell death in HBMEC is a mechanism some pathogens employ, presumably to gain entrance into the CNS by an impairment of BBB integrity [2327].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is classically understood to be initiated by early pro-inflammatory cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and IL-8 [23]. However, recent studies have suggested an interlinkage of apoptosis and inflammation, proposing a crucial role for caspases in both [24, 25]. Whereas caspases 3, 8, and 9 are among those primarily involved in apoptosis, caspases 4 and 5 mediate inflammatory responses and pyroptosis as an inflammatory form of cell death [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…The present study identified a total of 11 coexpressed mRNAs. IL1B ( 46 ), SP100 Nuclear Antigen ( 47 ), FAS ( 48 ) and TLR3( 49 ) are mRNAs that are regulators that modulate the inflammatory and immune responses. The possibility that linc-LPA-1 serves a role in the inflammatory and immune responses in MFS by regulating mRNA expression levels requires further investigation.…”
Section: Discussionmentioning
confidence: 99%